Aberrant p53 expression is associated with neoplastic progression in Barrett oesophagus diagnosed as indefinite for dysplasia. Issue 3 (3rd November 2022) - Chen, Xiuxu; Liu, Bella Lingjia; Harpaz, Noam; Zhu, Hongfa; Polydorides, Alexandros D.; Liu, Qingqing
Abstract : The aim of this study was to investigate the role of immunohistochemical (IHC) expression of p53 and other potential clinical parameters as prognostic markers for predicting neoplastic progression in Barrett oesophagus (BE) patients diagnosed as indefinite for dysplasia (IND). The study included patients with established BE of any extent who had a diagnosis of IND accompanied by concurrent p53 immunohistochemistry (IHC) stain at the index endoscopic procedure and at least one follow‐up examination between 2000 and 2021. Correlation between disease progression from IND to higher‐grade dysplasia [low‐grade dysplasia (LGD), high‐grade dysplasia (HGD) and oesophageal adenocarcinoma (EAC)] and clinicopathological parameters were analysed. A total of 149 patients (99 males; mean age 63.3 ± 10.0 years, range = 35–89) were included in the final analysis. Median follow‐up was 37.1 months [interquartile range (IQR) = 20.5–59.1 months]. Progression rates from IND to LGD and HGD were 12.1% (18 of 149) and 2.7% (four of 149), respectively. On multivariate analysis, the number of IND diagnoses was significantly associated with progression to both LGD and HGD ( P  = 0.016 and P  < 0.001, respectively). Cox regression analysis showed that aberrant p53 expression was significantly associated with progression to LGD [hazard ratio (HR) = 4.87, 95% confidence interval (CI) = 1.91–12.45, P  = 0.001] and HGD (HR = 21.81, 95% CI = 1.88–253.70, P  = 0.014). Kaplan–Meier survival analysis also demonstrated that aberrant p53 expression was significantly associated with progression to LGD ( P  < 0.001) and HGD ( P  = 0.001). Our results suggest that frequency of IND diagnoses and status of p53 expression can help to stratify risk of neoplastic progression in BE patients with IND. Abstract : The study included 149 BE patients with IND, 119 with wild‐type and 30 with aberrant p53 expression at baseline. During a median follow‐up of 37.1 months, the number of IND diagnoses on surveillance endoscopies was associated with progression to LGD ( P  = 0.016) and HGD ( P  < 0.001) and aberrant p53 expression was associated with progression to LGD ( P  < 0.001) and HGD ( P  = 0.001).